Up-regulation of MIAT aggravates the atherosclerotic damage in atherosclerosis mice through the activation of PI3K/Akt signaling pathway. (1st January 2019) - Sun, Guoqiang; Li, Yubo; Ji, Zhiyong
Abstract: This study is performed to elucidate the role of long non-coding RNA myocardial infarction associated transcript (lncRNA MIAT) in vulnerable plaque formation in rats with atherosclerosis (AS) through the regulation of the PI3K/Akt signaling pathway. The mice model of AS was established, and the successful modeled AS mice were treated with overexpressed MIAT and silenced MIAT. The levels of blood lipids, atherosclerotic plaques (AP) formation, the lipid content, collagen content, apoptosis of aortic cells, angiogenesis as well as the expression of inflammatory factors, such as tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) were determined through a series of experiments. MIAT was found to be upregulated in AS. Additionally, MIAT up-regulated the levels of blood lipids, promoted AP formation, increased the lipid content and decreased the collagen content of AP, promoted the apoptosis of aortic cells in AS mice by activating the PI3K/Akt signaling pathway. Meanwhile, MIAT was determined to promote angiogenesis as well as the expression of inflammatory factors (IL-1β, IL-6, and TNF-α) in AS mice through the activation of the PI3K/Akt signaling pathway. Furthermore, MIAT activated the PI3K/Akt signaling pathway to participate in AS progression. Our study suggests that upregulation of MIAT can aggravate AS injury in AS mice via the activation of the PI3K/Akt signaling pathway, which could provide a novel target for the treatment of AS.